Paparan Mikroplastik yang Berdampak pada Gangguan Sistem Pencernaan, Saraf, Pernafasan, Disfungsi Organ, dan Perkembangan Kehamilan - Ni Nyoman Trijayanti; Ni Made Sri Nopiyanti (Journal of Telenursing (JOTING), 2026)
This study aims to examine the scientific evidence regarding the health impacts of microplastic. The method used is secondary research with a literature review design following the PRISMA guidelines. The literature search was conducted through the PubMed and Google Scholar databases. A total of 10 articles meeting the inclusion and exclusion criteria. The results show that microplastic exposure causes multisystem health disorders. In the digestive system, microplastics alter the composition of gut microbiota and damage the intestinal epithelium. In vital organs, liver inflammation, lipid metabolism disorders, and lung tissue. Furthermore, microplastics can penetrate the placenta, thereby disrupting fetal development and causing neurotoxic effects on the central nervous system. The main mechanisms of this damage involve oxidative stress, systemic inflammation, and biological barrier dysfunction. In conclusion, microplastic exposure is proven to have significant negative impacts on the digestive, respiratory, nervous, reproductive, and cardiovascular systems.   Keywords: Human health, Microplastics, Nanoplastics, Organ dysfunction